Montelukast for Migraine Prophylaxis: A Randomized, Double-Blind, Placebo-Controlled Study - Brandes, Jan L.; Visser, W. Hester; Farmer, Mildred V.; Schuhl, Amy L.; Malbecq, William; Vrijens, France; Lines, Christopher R.; Reines, Scott A. (Headache, 2004)
Objective.—To evaluate the efficacy and tolerability of montelukast 20 mg in the prophylactic treatment of migraine. Background.—A previous small open‐label study in migraine patients suggested prophylactic efficacy for montelukast, an antagonist of the cysteinyl leukotriene receptor that is used in the treatment of asthma. We sought to confirm these findings in a randomized controlled trial. Methods.—This multicenter, randomized, double‐blind, placebo‐controlled, parallel‐groups study enrolled adult migraine outpatients who experienced ≥3 and ≤8 migraine attacks per month for the last 6 months. Patients were entered into a 2‐month, single‐blind, placebo run‐in phase. Only patients who experienced ≥3 migraine attacks in the second month were eligible to enter the subsequent 3‐month, double‐blind treatment phase of the study. The primary efficacy endpoint was the percentage of patients reporting at least a 50% decrease in migraine attack frequency per month during the double‐blind treatment period (months 3‐5) compared to baseline (run‐in month 2). Results.—A total of 93 patients were randomized to montelukast 20 mg and 84 patients to placebo at the end of the placebo run‐in month 2; 76 patients on montelukast and 72 patients on placebo completed the double‐blind treatment period. Over 3 months of treatment, there was no significant difference between the two groups in the percentage of patients who reported at least a 50% decrease in migraine attack frequency per month: 15.4% for montelukast versus 10.3% for placebo (P= .304). In addition, montelukast 20 mg was not significantly superior to placebo on any of the secondary endpoints. There were no differences between treatment groups for adverse events. Conclusion.—Montelukast 20 mg was well tolerated in migraine patients but was not an effective prophylactic for prevention of migraine.